POLITIK FAMILISME DI TUBUH PARTAI ISLAM LOKAL: STUDI KASUS PARTAI PERSATUAN PEMBANGUNAN (PPP) KABUPATEN REMBANG - Azahra, Jihan Marsya; Alfirdaus, Laila Kholid (Journal of Politic and Government Studies, 2019)
The politics of familism is interesting to discuss because it is relatively a common phenomenon in Indonesia, but is hardly revelaed through academic lens. In practice,2 it is not rare to find a group of families drives a party machine through the party’s organizational structure, legislature body, and the other related decision making. this article is based on a case study in Partai Persatuan Pembangunan (PPP) in Rembang regency, Central Java, in which two big religious scholars’ families, namely KH. Maemoen Zubair and the late KH. Ahmad Thoyfoer have significant influences in the PPP’s political movement both in local and national level. This article proposas a question on how the practice of familism is constructed within the party’s body, and the implication on party’s institutional governance. The research applied participatory observation through direct involvement in party’s activities, in-depth interviews and documentary studies. This research found that familism is inseparable in party’s body. It is built through the involvement of relatives in party’s organization as well as kyai-santri relationships. Further, familism is found to bring traditional culture in political party’s governance.Keywords: The Politics of Familism, Patron-client, Kyai, Santri and Political Culture